PSR J1755−2550: a young radio pulsar with a massive, compact companion. Issue 4 (23rd February 2018) - Ng, C; Kruckow, M U; Tauris, T M; Lyne, A G; Freire, P C C; Ridolfi, A; Caiazzo, I; Heyl, J; Kramer, M; Cameron, A D; Champion, D J; Stappers, B
Abstract: Radio pulsars found in binary systems with short orbital periods are usually fast spinning as a consequence of recycling via mass transfer from their companion stars; this process is also thought to decrease the magnetic field of the neutron star being recycled. Here, we report on timing observations of the recently discovered binary PSR J1755−2550 and find that this pulsar is an exception: with a characteristic age of 2.1 Myr, it is relatively young; furthermore, with a spin period of 315 ms and a surface magnetic field strength at its poles of 0.88 × 10 12 G, the pulsar shows no sign of having been recycled. Based on its timing and orbital characteristics, the pulsar either has a massive white dwarf (WD) or a neutron star (NS) companion. To distinguish between these two cases, we searched radio observations for a potential recycled pulsar companion and analysed archival optical data for a potential WD companion. Neither work returned conclusive detections. We apply population synthesis modelling and find that both solutions are roughly equally probable. Our population synthesis also predicts a minimum mass of 0.90 M⊙ for the companion star to PSR J1755−2550 and we simulate the systemic runaway velocities for the resulting WDNS systems which may merge and possibly produce Ca-rich supernovae. Whether PSR J1755−2550 hosts a WD or a NS companion star, it is certainly a member of a rare subpopulation of binary radio pulsars.